Implementasi Algoritma YOLOv5 dalam Mendeteksi Penggunaan Masker Pada Kantor Biro Umum Gubernur Sulawesi Barat - Muhammad Harun Ashar; Dedi Suarna (STMIK Budi Darma, 2022)
The implementation of health protocols, especially the uses of masks, is an obligation that must be carried out by the people in Indonesia at that time in preventing the Covid-19 Pandemic. However, in practice it is still common to find various non-compliances by the community in carrying out their obligation to wear masks when outside the home. This study aims to see how the performance of the YOLOv5 algorithm in detecting the use of masks in the community specifically at the West Sulawesi Province is an area that is always visited by many regional employees of the Province of West Sulawesi. The results obtained are that the YOLOv5 algorithm can detect multiple images of one person or multiple people in one image. It can be seen from the implementation results in the West Sulawesi governor's office environment, it can be seen from the video that the results of the prediction box are correct in detecting the image of a mask on the face